The Significance of al-Ghazālī and His Works for Indonesian Muslims: A Preliminary Study - Said, Nurman (Studia Islamika, 1996)
Abu Hamid Muhammad al-Ghazali (1058-1111) was a unique figure in the intellectual history of Islam. In this article will be reviewed several factors that made al-Ghazali had a fascination for the Indonesian Islamic community. The author reveals that the appeal of al-Ghazali's thought is its success in integrating the formal religious teachings with internal spiritual appreciation.DOI: 10.15408/sdi.v3i3.799